The Arabidopsis RNA Polymerase II Carboxyl Terminal Domain (CTD) Phosphatase-Like1 (CPL1) is a biotic stress susceptibility gene - Thatcher, L.; Foley, R.; Casarotto, H.; Gao, L.; Kamphuis, Lars; Melser, S.; Singh, Karam (Nature Publishing Group, 2018)
© 2018, The Author(s). Crop breeding for improved disease resistance may be achieved through the manipulation of host susceptibility genes. Previously we identified multiple Arabidopsis mutants known as enhanced stress response1 (esr1) that have defects in a KH-domain RNA-binding protein and conferred increased resistance to the root fungal pathogen Fusarium oxysporum. Here, screening the same mutagenized population we discovered two further enhanced stress response mutants that also conferred enhanced resistance to F. oxysporum. These mutants also have enhanced resistance to a leaf fungal pathogen (Alternaria brassicicola) and an aphid pest (Myzus persicae), but not to the bacterial leaf pathogen Pseudomonas syringae. The causal alleles in these mutants were found to have defects in the ESR1 interacting protein partner RNA Polymerase II Carboxyl Terminal Domain (CTD) Phosphatase-Like1 (CPL1) and subsequently given the allele symbols cpl1-7 and cpl1-8. These results define a new role for CPL1 as a pathogen and pest susceptibility gene. Global transcriptome analysis and oxidative stress assays showed these cpl1 mutants have increased tolerance to oxidative stress. In particular, components of biotic stress responsive pathways were enriched in cpl1 over wild-type up-regulated gene expression datasets including genes related to defence, heat shock proteins and oxidative stress/redox state processes.